A Qualitative Study of Barriers to Effectiveness of Interventions to Prevent Mother-to-Child Transmission of HIV in Arba Minch, Ethiopia. (8th July 2012) - Adedimeji, Adebola; Abboud, Nareen; Merdekios, Behailu; Shiferaw, Miriam
Abstract : Objectives . Despite the availability of services to prevent mother-to-child transmission (PMTCT) of HIV, socio-cultural, health system and operational factors constrain many pregnant women from accessing services or returning for followup thereby increasing the risk of vertical transmission of HIV to newborns. We highlight and describe unique contextual factors contributing to low utilization of PMTCT services in Arba-Minch, Ethiopia. Methods . Qualitative research design was utilized to obtain data through focus group discussions and in-depth interviews with antenatal clinic attendees, health workers health facilities in the study area. Results . Awareness of PMTCT services and knowledge of its benefits was nearly universal, although socioeconomic, cultural and health system factors, including stigma and desire to prevent knowledge of serostatus, impede access to and utilization of services. Health system factors—lack of appropriate followup mechanisms, inadequate access to ARV drugs and poorly equipped manpower also contribute to low utilization of services. Conclusion . Reducing mother-to-child transmission of HIV in sub-Saharan Africa will be more effective when unique contextual factors are identified and addressed. Effectiveness of PMTCT interventions rests on a well functioning health system that recognize the importance of social, economic, cultural contexts that HIV positive pregnant women live in.